HILANGNYA VISI MORAL GEREJA DI ERA PASCAMODERN: STUDI ANALITIS TERHADAP PEMIKIRAN DAVID F. WELLS DAN RELEVANSINYA BAGI PERANAN GEREJA DI INDONESIA - Jamson Siallagan (Manna Rafflesia, 2025)
This research, aims to analyze David F. Wells' thoughts about the loss of moral vision in the American evangelical church as a result of postmodern influence. By using descriptive analysis method, it is found that the church which has lost its moral vision is characterized by the existence of a postmodern spirituality which only focuses on subjective experience for self-satisfaction. The church tends to give priority to personality which emphasizes an attractive, alluring, and alluring self-image, without paying attention to virtue-related characters based on God's higher moral law. The writer finds the relevance of Wells's thought for the church in Indonesia so that the church can carry out the role as a moral agent. This relevance includes the church must have the right understanding and attitude towards postmodernism, a strong theological understanding based on the truth of God as the source and center of the church's morals, the formation of the character of the congregation based on God's truth as a standard of ethical behavior, an understanding of true faith as the basis for people's involvement Christianity in society, and good church stewardship to present moral beauty.